2018
DOI: 10.1007/s11013-018-9574-y
|View full text |Cite
|
Sign up to set email alerts
|

René Girard and the Mimetic Nature of Eating Disorders

Abstract: French historian and literary critic René Girard (1923–2015), most widely known for the concepts of mimetic desire and scapegoating, also engaged in the discussion of the surge of eating disorders in his 1996 essay Eating Disorders and Mimetic Desire. This article explores Girard’s ideas on the mimetic nature and origin of eating disorders from a clinical psychiatric perspective and contextualizes them within the field of eating disorders research as well as in relation to broader psychological, sociological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…French historian and cultural critic René Girard proposed the theory of peer-based ‘mimetic desire’ to account for the onset and perpetuation of anorexia. 23 Girard suggested that desire is mimetic: since humans learn by imitating others, our desires may be based on what we perceive that other people most want. In adolescence, the desire for thinness emanates from westernised culture through ‘the people who really count in our adolescence and who are our peers and contemporaries’.…”
Section: Recovery During Emerging Adulthoodmentioning
confidence: 99%
“…French historian and cultural critic René Girard proposed the theory of peer-based ‘mimetic desire’ to account for the onset and perpetuation of anorexia. 23 Girard suggested that desire is mimetic: since humans learn by imitating others, our desires may be based on what we perceive that other people most want. In adolescence, the desire for thinness emanates from westernised culture through ‘the people who really count in our adolescence and who are our peers and contemporaries’.…”
Section: Recovery During Emerging Adulthoodmentioning
confidence: 99%
“…These, he claimed, were fairly easily explained as a manifestation of the universal desire for thinness. In contrast to the prevailing—and complex—psycho‐dynamic or bio‐psycho‐social explanations (Strand, ), Girard argues that eating disorders are an example of mimesis taking on the form of “conspicuous non‐consumption” (Girard, , p. 10). He uses these disorders as an example of what can happen when the braking mechanism of scapegoating is not used or not available (Strand, ).…”
Section: Applications Of Mimetic Theory To Mental Illnessmentioning
confidence: 99%
“…In contrast to the prevailing—and complex—psycho‐dynamic or bio‐psycho‐social explanations (Strand, ), Girard argues that eating disorders are an example of mimesis taking on the form of “conspicuous non‐consumption” (Girard, , p. 10). He uses these disorders as an example of what can happen when the braking mechanism of scapegoating is not used or not available (Strand, ). Strand () critiques Girard's conceptualization as suffering from “a lack of openings towards alternative possibilities….it is very hard to picture a way out, to imagine a space for treatment and recovery” (p.575).…”
Section: Applications Of Mimetic Theory To Mental Illnessmentioning
confidence: 99%
See 2 more Smart Citations